Analysis of influencing factors and construct a prediction model for postoperative intestinal obstruction of colorectal cancer - Wang Zhen; Chen Linyun; Wang Lin; He Hongqin; Mou Kaidong; Liu Feng (结直肠肛门外科)
[Objectives] To analyze the influencing factors for postoperative intestinal obstruction of colorectal cancer and construct a prediction model. [Methods] A retrospective analysis was conducted on 300 patients with colorectal cancer admitted to our hospital from March 2020 to March 2023. They were divided into an observation group (with intestinal obstruction, n＝28) and a control group (without intestinal obstruction, n＝272) based on whether intestinal obstruction occurred after surgery. General information, perioperative related indicators, and levels of C-reactive protein (CRP), procalcitonin (PCT), and interleukin-6 (IL6) before surgery, on the day of surgery, the 3rd day and the 5th day after surgery were compared between the two groups. LASSO regression analysis was used to screen variables for intestinal obstruction after colorectal cancer surgery, and multivariate Logistic regression analysis was used to investigate the independent risk factors for intestinal obstruction after colorectal cancer surgery. A nomogram prediction model for intestinal obstruction after colorectal cancer surgery was constructed. The receiver operating characteristic curve (ROC) and calibration curve were drawn to evaluate the prediction ability and goodness of fit of the model. [Results] The proportions of patients with tumor location in the rectum, tumor stage Ⅲ, preoperative intestinal obstruction, laparotomy and conversion laparotomy, as well as tumor diameter, were higher in the observation group than in the control group (P<0.05). The levels of CRP, PCT, and IL6 on the day of surgery, the 3rd day and the 5th day after surgery were higher in the observation group than in the control group (P<0.05), and the measurement time had no effect on the levels of postoperative CRP, PCT, and IL6 (P>0.05). LASSO regression analysis showed that tumor stage, preoperative intestinal obstruction, surgery type, and levels of CRP, PCT, and IL6 on the 5th day after surgery were variables for intestinal obstruction after colorectal cancer surgery. Multivariate Logistic regression analysis showed that tumor stage Ⅲ, preoperative intestinal obstruction, laparotomy and conversion laparotomy, and levels of CRP, PCT, and IL6 on the 5th day after surgery were independent risk factors for intestinal obstruction after colorectal cancer surgery (P<0.05). The C-index of the nomogram prediction model was 0.865, the area under the ROC curve (AUC) was 0.865 (95%CI: 0.799-0.902), and the C-index of the calibration curve was 0.814, indicating good consistency between the model and the actual observations. [Conclusion] Tumor stage Ⅲ, preoperative intestinal obstruction, laparotomy and conversion laparotomy, and levels of CRP, PCT, and IL6 on the 5th day after surgery are independent risk factors for intestinal obstruction after colorectal cancer surgery. The nomogram model constructed based on these factors has good predictive ability and can provide an important reference for clinically predicting intestinal obstruction after colorectal cancer surgery.